Insights Into the Pathogenesis of Sweet's Syndrome - Heath, Michael S.; Ortega-Loayza, Alex G. (Frontiers in Immunology, 2019)
Sweet’s syndrome, also known as Acute Febrile Neutrophilic Dermatosis, is a rare inflammatory condition. It is considered to be the prototype disease of neutrophilic dermatoses, and presents with acute onset dermal neutrophilic lesions, leukocytosis and pyrexia. Several variants have been described both clinically and histopathologically. Classifications include classic Sweet’s syndrome, malignancy associated, and drug induced. The cellular and molecular mechanisms involved in Sweet’s syndrome have been difficult to elucidate due to the large variety of conditions leading to a common clinical presentation. The exact pathogenesis of Sweet’s syndrome is unclear; however, new discoveries have shed light on the role of inflammatory signaling, disease induction, and relationship with malignancy. These findings include an improved understanding of inflammasome activation, malignant transformation into dermal infiltrating neutrophils, and genetic contributions. Continued investigations into effective treatments and targeted therapy will benefit patients and improve our molecular understanding of inflammatory diseases, including Sweet’s syndrome.